Land Processing Procedure (Texas Journal of Engineering and Technology, 2024)
The purpose of tillage is that tillage processes in various forms have been practiced since the first primitive period of plant cultivation. Primitive man used tools to stir the soil to plant the seeds. It means plowing the land and growing grain. Jethrotull, considered the father of tillage, said that thorough plowing was necessary to break up the soil into fine pieces. creates conditions. Tillage is the physical condition of soil resulting from tillage